A METHOD FOR DELIMBING TREE-TRUNKS AND A DEVICE FOR APPLYING THE METHOD - Rukomojnikov, Konstantin; Vedernikov, Sergei; Gabdrahmanov, Marsel (Journal of Applied Engineering Science, 2018)
The article is devoted to improve the quality of delimbing tree-trunks by means of time-effective bringing it into an operational position before contact with the branches. The set goal is achieved as a result of brining the delimbing knife into operational mode, parallel to the direction of the tree-trunk feed motion, following the load shift of the pusher beyond the cutting edge. This type of load emerges when the branches press upon the pusher. After the stress finishes both the mechanisms return to their original position. The described method and the construction of the mechanism allow to move the delimbing knife in the operational position, thus enhancing the delimbing quality.
Keywords: tree; delimbing knives; dissipative forces; harvester head; forestry machinery